Counter-hegemonic contra-flow and the Al Jazeera America fiasco: A social network analysis of Al Jazeera America's Twitter users. (December 2017) - Samuel-Azran, Tal; Hayat, Tsahi
Al Jazeera America, arguably the most ambitious attempt in history by a non-Western network to broadcast to US audiences, was shut in April 2016. A social network analysis of Al Jazeera America's following on Twitter reveals that 42 per cent of Al Jazeera America's followers did not follow any other US news outlet and that most of the remaining 58 per cent followed liberal stations. The findings illustrate mainstream US news consumers' reluctance to follow Al Jazeera America, which only appealed to specific audiences. The analysis portrays the challenges facing counter-hegemonic contra-flow stations such as Al Jazeera America in their bid to gain legitimacy in the West, and specifically in the United States, and highlights the relevance of selective exposure and hostile media theories in the case of counter-flowing stations.